2021
DOI: 10.1002/ijc.33478
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and breast cancer risk in Japan: A pooled analysis of eight population‐based cohort studies

Abstract: Although alcohol consumption is reported to increase the incidence of breast cancer in European studies, evidence for an association between alcohol and breast cancer in Asian populations is insufficient. We conducted a pooled analysis of eight large‐scale population‐based prospective cohort studies in Japan to evaluate the association between alcohol (both frequency and amount) and breast cancer risk with categorization by menopausal status at baseline and at diagnosis. Estimated hazard ratios (HR) and 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…A meta-analysis of a prospective study showed that total fiber (especially soluble fiber) consumption was associated with an 8% lower risk of breast cancer 57 . Moreover, in a study of an Asian population, regular consumption of Lactobacillus casei Shirota (BLS), soy isoflavone, and vitamin D reduced breast cancer risk in premenopausal women, whereas alcohol consumption was significantly associated with a higher risk of breast cancer, specifically in premenopausal women 58 60 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of a prospective study showed that total fiber (especially soluble fiber) consumption was associated with an 8% lower risk of breast cancer 57 . Moreover, in a study of an Asian population, regular consumption of Lactobacillus casei Shirota (BLS), soy isoflavone, and vitamin D reduced breast cancer risk in premenopausal women, whereas alcohol consumption was significantly associated with a higher risk of breast cancer, specifically in premenopausal women 58 60 .…”
Section: Discussionmentioning
confidence: 99%
“…When aggregated, however, these risk alleles together would likely indicate substantial risk elevation in those in the high-risk group. In previous studies in Japanese females, the impact of genetic risk in the high-risk groups was larger than that of cigarette smoking, alcohol drinking and obesity [47][48][49][50]. Unlike smoking, drinking and obesity, however, genetic risk cannot be modified.…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have also shown a positive relationship between alcohol consumption and an increased risk of breast cancer [31][32][33][34]. A Japanese study that shed more light on the effects of alcohol consumption on breast cancer found that the risk was greater only in premenopausal women [35]. Unfortunately, despite the fact that many studies on alcohol consumption among adult women have been conducted in the context of breast cancer, little research has focused on the effects of alcohol consumption in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%